INSAT: uma proposta metodológica para análise dos efeitos das condições de trabalho sobre a saúde - Carla Barros-Duarte; Liliana Cunha; Marianne Lacomblez (Universidade do Porto, 2007)
The problematic involving health and work relations is not new in itself. Actually, it has been a source of many studies and interventions in several EU countries. This research field is particularly interesting also due to the compulsory compliance with the legislation and to a greater awareness of the effects of professional risks.Understanding work consequences on workers´ health and well being benefits from the development of an integrated analysis centred on workers´ point of view and their working conditions. The tool we are presenting, the Health and Work Inquiry (INSAT), is based on other inquiries. Nevertheless, it gives a distinctive contribution to this integrated and worker-centred approach and also aims at promoting workers´ reflections on the consequences of work conditions, making these effects more explicit in their statements.